2010
DOI: 10.1007/s11999-009-1143-9
|View full text |Cite
|
Sign up to set email alerts
|

Delta Ceramic-on-Alumina Ceramic Articulation in Primary THA: Prospective, Randomized FDA-IDE Study and Retrieval Analysis

Abstract: Wear and osteolysis continue to be major reasons for revision surgery in THA. Ceramic-on-ceramic bearings eliminate polyethylene wear debris. The newest generation of these bearings incorporate nanosized, yttriastabilized tetragonal zirconia particles producing an alumina matrix composite. We asked whether this new material would perform as well as a conventional bearing in terms of functional hip scores, radiographic migration and osteolysis, complications and survival. As part of a US FDA investigational dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 44 publications
2
60
0
4
Order By: Relevance
“…During the past decade, various studies have reported outcomes and survival of alternative bearing surfaces in THA [6,7,9,12,14,15,19,20,[23][24][25]. Complications associated with the use of hard-on-hard bearings include squeaking, fracture, liner disassociation, metallosis, and hypersensitivity reactions occurring in some patients [14].…”
Section: Discussionmentioning
confidence: 99%
“…During the past decade, various studies have reported outcomes and survival of alternative bearing surfaces in THA [6,7,9,12,14,15,19,20,[23][24][25]. Complications associated with the use of hard-on-hard bearings include squeaking, fracture, liner disassociation, metallosis, and hypersensitivity reactions occurring in some patients [14].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, improvements in manufacturing processes have produced ceramics with smaller grain sizes, lower porosity, and higher density, leading to stronger and more fractureresistant materials [29]. This may lead to component fracture rates as low as one in 25,000 in some reports [35]; however, it remains to be determined whether these design modifications will actually decrease fracture rates [24]. Because the incidence of fracture may have been reduced, the current thought is that the primary cause of failure in ceramic-on-ceramic bearings is now due to increased wear rates related to component malpositioning [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies with various follow-up durations have compared C-C bearings with C-P bearings 15,[32][33][34][35][36][37] ; most had both baseline and postoperative measurements. In addition, one trial compared C-C with M-P bearings; this had only postoperative measurements [11][12][13][14] .…”
Section: Discussionmentioning
confidence: 99%